1997
DOI: 10.1093/ndt/12.10.2099
|View full text |Cite
|
Sign up to set email alerts
|

Serological evidence for reactivation of EBV infection due to uraemic immunodeficiency

Abstract: We conclude that determination of E1/E2 is useful for assessment of EBV infection in patients with chronic renal failure and 'uraemic immunodeficiency'. In patients with immunosuppressive therapy following renal transplantation additional testing including direct estimation of viral load, is necessary to correctly assess the state of EBV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 0 publications
1
5
0
1
Order By: Relevance
“…Both cancers are known to be associated with human papillomavirus (HPV) and it has been postulated that uremic immune dysfunction, supported by the evidence of reactivation of latent Epstein-Barr virus infection in uremic immunodeficiency [27] could be a possible cause. In addition, the use of immunosuppressive agents during treatment of the underlying diseases leading to ESKD could also result in a higher risk of these HPV-related cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Both cancers are known to be associated with human papillomavirus (HPV) and it has been postulated that uremic immune dysfunction, supported by the evidence of reactivation of latent Epstein-Barr virus infection in uremic immunodeficiency [27] could be a possible cause. In addition, the use of immunosuppressive agents during treatment of the underlying diseases leading to ESKD could also result in a higher risk of these HPV-related cancers.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 This explanation is supported by evidence of reactivation of latent Epstein-Barr virus infection in uremic immunodeficiency. 21 A contributing factor may be the use of immunosuppressive agents to treat diseases that cause ESKD.…”
Section: Commentmentioning
confidence: 99%
“…The anti-EBNA-1/anti-EBNA-2 ratio also was examined, with a ratio of Յ 1.0 considered as serologic evidence of a deregulated immune response in other clinical settings. [4][5][6][7][8][9] Masked repeat samples (5% of specimens) were included to enable monitoring of within-batch reproducibility of antibody titers. The withinbatch coefficients of variation from the blind quality control samples were 9.9% for anti-VCA, 38.9% for anti-EA complex, 12.4% for anti-EBNA complex, 16.8% for anti-EBNA-1, and 37.5% for anti-EBNA-2.…”
Section: Serologic Specimens and Assaysmentioning
confidence: 99%
“…5 Persistent anti-EBNA-1/anti-EBNA-2 antibody ratios of Յ 1.0 have been described in patients with inherited immunologic disorders, severe infectious mononucleosis, chronic EBV infection, rheumatoid arthritis, chronic renal failure, and AIDS. [4][5][6][7][8][9] Recently, it has been shown that an anti-EBNA-1/EBNA-2 ratio Յ 1.0 is associated with Hodgkin lymphoma risk, independent of a history of infectious mononucleosis. 10 Henle et al have suggested that this atypical pattern is indicative of inadequate host regulation of latent EBV infection.…”
Section: Introductionmentioning
confidence: 99%